Audit Quality Influencing Factors : comparative study between Islamic and conventional banks in Malaysia - Eddine, Chaabane Oussama Houssem (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2012)
Corporate scandals and fraud have, without any doubt, a direct relation to the level of audit quality provided by the audit firm. Therefore, it is important that the highest possible level of audit quality is maintained, especially in banks as they are fundamental to the strength and stability of a country's economy. Although audit quality in banks is crucial, accounting research tends to focus on disclosure practices or performance measures of these banks. Thus research on audit quality of banks is lacking, particularly in relation to Islamic banks. Research on audit quality may be restricted by the fact that it is difficult to measure, especially for the stakeholders of these banks as they are not part of the audit firm. Nevertheless, there are indicators of audit quality, which are termed as Audit Quality Influencing Factors (AQIF) in this study, and used to obtain an indication of audit quality in Malaysian banks. Also, since Islamic institutions accord all its activities to the principle of Islamic accountability, and have to be accountable to more stakeholders, and ultimately God, this study expects that the level of audit quality in Islamic banks will be higher than conventional ones. Therefore, this study investigates the difference between AQIF of Islamic banks and conventional banks in Malaysia. In addition the study also determines whether there has been an improvement in AQIF in the Malaysian banks in 2009 as compared to 2006.This study analyzes Islamic and conventional banks, 20 banks in 2006 and 33 banks in 2009, listed on Bursa Malaysia. The results of this study found that there is no difference between Islamic and conventional banks' in terms of AQIF. The findings indicate as well that Islamic banks had witnessed significant improvement in their AQIF while conventional banks have not experienced an improvement in most of their AQIF.